Feeding habits of larval fishes of the family Clupeidae (Actinopterygii: Clupeiformes) in the estuary of River Pendas, Johor, Malaysia. - Ara, Roushon; Arshad, Aziz; Musa, L.; Nurul Amin, Sanker Mohammad; Kuppan, Perumal (Academic Journals, 2011)
Studies on feeding habits and seasonal variation of diet of fish larvae of family Clupeidae was conducted from October 2007 to September 2008 in the estuary of Sg. Pendas, Gelang Patah, Johor, Malaysia. The diet composition were grouped into seven major categories consisted of phytoplankton, zooplankton, plant-like matter, debris, fragment of copepod, algae and unidentified food items. The most predominant food items in the gut of clupeids was phytoplankton (82.53%), followed by plant-like matter (7.34%), debris (4.86%), fragment of copepods (2.69%), algae (0.92%), unidentified items (0.77%) and zooplankton (0.54%).